A novel procedure for damage evaluation of fillet-welded joints. (July 2020) - Vantadori, Sabrina; Iturrioz, Ignacio; Carpinteri, Andrea; Greco, Fabrizio; Ronchei, Camilla
Highlıghts: A procedure for fatigue life assessment of fillet-welded joints is proposed. The procedure exploits a multiaxial fatigue criterion for complex random loading. Experimental data related to a T-joint are used to validate the novel procedure. Such a T-joint is the weakest link of an arm sprayer used in agriculture. The crack nucleation location on the weld toe is numerically evaluated. Abstract: In the present paper, a novel procedure for fatigue resistance assessment of fillet-welded joints under complex random loading is proposed. It consists of two consecutive steps: (1) computation of the stress tensor at the verification point; (2) evaluation of damage and, consequently, fatigue life. The procedure exploits the multiaxial critical plane-based criterion by Carpinteri et al. for random loading. A case study, represented by a mechanical component of an arm sprayer used in agriculture, is examined in order to assess such a procedure. A comparison between experimental and numerical results in terms of crack nucleation location is performed.